Taman Sehat dalam Kegiatan Kampus Mengajar di SD 116 Rejang Lebong - Febriani, Zahara; Lestari, Fitri; Yanuarti, Mira (Kreativasi : Journal of Community Empowerment, 2024)
In the context of Elementary School 116 Rejang Lebong, this program aims to encourage healthy gardening methods and good yard land utilization. The first step in the activity's implementation is a socializing exercise in the garden that involves planting real plants including gotu kola, aloe vera, ginger, cat whiskers, and lemongrass. Additionally, media preparation and land planting are done in the educational setting. Students are able to use yard land and comprehend the value of live pharmaceutical plants as a result of this project.